The Effect of Experiental Marketing on Cafe Excelso Customer Loyalty in Central Jakarta 2019 - Rina Ayu Vildayanti (JABE (Journal of Applied Business and Economic), 2020)
This study aimed to analyze the influence of experiential marketing on customer loyalty Cafe Excelso in Central Jakarta 2019. The research methodology used is quantitative method with cross section data and primary data obtained from questionnaires. The sampling technical using purposive sampling method with the data in 2019. The data analysis technique used is multiple linear regression to test of the validity, reliability test, classic assumption test (multicollinearity test, heteroscedasticity test) and hypothesis testing t-statistic and f-statistic to examine the effect together with a significance level of 5%. The results of this study indicate that in partial sense, feel, think, and act positive and significant impact on the customer loyalty, while relate variable have negative effect but not significant on customer loyalty. Meanwhile simultaneous independent variable sense, feel, think, act, and relate togetherly have a significant relationship to the dependent variable which is customer loyalty. Coefficient of determination from this study showed that the number of 71.96% of the variation of the independent vaiable sense, feel, think, act, and relate is able to explain the variation of the rise and fall dependent variable customer loyalty by 71.96%, while the remaining 28.04% influenced by other independent variable.Keywords : Experiential Marketing, Sense, Feel, Think. Act, Relate, Customer Loyalty.